Tendencia de la recaudación de impuestos al consumo en la región Loreto periodo 2020-2024 - Chumbe Gonzales, John Alfredo (2025)
Exemptions to consumption tax in the Loreto region, along with informality, tax ignorance, and geographical barriers, significantly reduce tax collection, affecting the State's ability to finance regional development. Therefore, this work aims to identify the trend in consumption tax collection in the Loreto region during the 2020-2024 period, considering a longitudinal quantitative approach and descriptive non-experimental design. This study included Loreto's 2020-2024 tax collection data as a population. The results show a mostly positive trend, reflecting a progressive recovery of economic activity after the effects of the pandemic. Total collection increased from S/ 54.84 million in 2020 to S/ 75.63 million in 2024, highlighting the strengthening of the Selective Consumption Tax (ISC), which showed sustained growth throughout the five years analyzed. In contrast, the General Sales Tax (IGV), while remaining the most significant tax, showed a more fluctuating trend, influenced by the continued existence of tax exemptions in the region. The Plastic Bag Consumption Tax (ICBP), although with a reduced share, registered an upward trend until 2023, with a slight decline in 2024, demonstrating its consolidation as a complementary environmental tax.